Pembelajaran Musik dalam Pendidikan Teologi: Pendampingan Mahasiswa Asal Papua di Sekolah Tinggi Teologi Katharos Indonesia Bekasi - Daniel Halomoan Marbun (Pusat Riset dan Inovasi Nasional, 2026)
This community service activity was motivated by differences in students’ learning responses in music learning at Sekolah Tinggi Teologi Katharos Indonesia, especially among Papuan students. Of the 17 students participating in music learning, 12 Papuan students demonstrated learning processes that required more intensive instructional adaptation compared to students from other regions. This community service program aimed to analyze the relationship between learning cultural background and the comprehension process of Papuan students in music learning within theological education. The research employed a qualitative approach with a case study design analyzed through Lev Vygotsky’s Social Constructivism theory. Data were collected through observation, additional learning sessions, and documentation of music learning activities using demonstration methods, active practice (learning by doing), audio-visual media, and participatory approaches. The results showed that students’ comprehension processes were influenced by educational background, previous learning experiences, limited understanding of music theory, and differences in learning styles. Contextual and participatory learning approaches were proven to improve learning engagement, tempo comprehension, and students’ confidence in music practice. The findings indicate that theological education institutions need to develop adaptive and contextual pedagogical strategies to bridge differences in students’ learning processes from diverse cultural backgrounds.